(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines common types of phishing attacks using Kazakhstan as an example, with the goal of raising awareness and suggesting effective protection measures against Internet scammers. The study analyzes the most popular phishing tactics used in the region. By identifying specific threats and vulnerabilities unique to Kazakhstan, the article strives to give readers a thorough understanding of the risks they face in the online environment. In addition to analyzing the situation with phishing, the article discusses preventive measures to protect citizens from such attacks. It provides practical insight into defense strategies, emphasizing both individual and collective efforts to improve cybersecurity resilience. The article is intended to provide readers with the knowledge necessary to recognize and mitigate potential threats. The findings and recommendations presented in this article serve as a valuable resource for individuals and businesses looking to strengthen their defenses against the ever-changing tactics used by online scammers.